An objective method of forecasting thunderstorm over Dundigal airfield and neighbourhood in the pre-monsoon season - SINGH, R. K. (MAUSAM, 1980)
In this study an attempt has been made to provide an objective method of forecasting thunderstorm activity over Dundigal airfield and neighbourhood during the pre-monsoon season (March to May). Inter-relationships of a number of meteorological parameters in the context of subsequent convective activity were studied by means of frequency tables. The six parameters, chosen were surface dew point, surface wind direction, Showalter stability index, wind direction at 850 mb, mean mixing ratio from 850 to 700 mb, and convective condensation level. These were combined graphically by correlation technique to form an objective forecasting aid. The method was tested on independent data and the results were found to be in good agreement with the observations. A skill score of 0.72 and a percentage accuracy of 87% were achieved.